Predictors of Permanent Pacemaker Implantation in Patients After Transcatheter Aortic Valve Replacement in a Chinese Population - Zhang, Jiaqi; Chi, Chengwei; Tian, Simiao; Zhang, Shulong; Liu, Jihong (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background：Permanent pacemaker (PPM) implantation is the main complication of transcatheter aortic valve replacement (TAVR). Few studies have evaluated the requirement for PPM implantation due to electrocardiogram (ECG) changes following TAVR in a Chinese population. Objective: Our study aimed to evaluate the incidence and predictors of PPM implantation in a cohort of Chinese TAVR patients. Methods: We retrospectively evaluated 39 consecutive patients with severe native aortic stenosis referred for TAVR with a self-expandable prosthesis, the Venus A valve (Venus MedTech Inc., Hangzhou, China), from 2019 to 2021 at the Heart Center of Affiliated Zhongshan Hospital of Dalian University. Predictors of PPM implantation were identified using logistic regression. Results: In our study, the incidence of PPM implantation was 20.5%. PPM implantation occurs with higher risk in patients with negative creatinine clearance (CrCl), dyslipidemia, high Society of Thoracic Surgeons (STS) Morbimortality scores and lead I T wave elevation. TAVR induced several cardiac electrical changes such as increased R wave and T wave changes in lead V5. The main independent predictors of PPM implantation were new-onset left bundle branch block (LBBB) (coef: 3.211, 95% CI: 0.899–7.467, p =0.004) and lead I T wave elevation (coef: 11.081, 95% CI: 1.632–28.083, p =0.016). Conclusion: New-onset LBBB and lead I T wave elevation were the main independent predictors of PPM implantation in patients undergoing TAVR. Clinical indications such as negative CrCl, dyslipidemia, high STS Morbimortality scores and an increased T wave elevation before TAVR should be treated with caution to decrease the need for subsequent PPM implantation.